The INFLUENCE OF MARKET ORIENTATION AND ENTREPRENEURSHIP ORIENTATION ON MODERATED COFFEE SHOP PERFORMANCE (M) SOCIAL MEDIA IN COFFEE SHOP IN JAMBI CITY - Zuhri, Almuluk Fajar; Fitriaty, Fitriaty; Indrawijaya, Sigit (Journal of Business Studies and Management Review, 2024)
This research aims to analyze the influence of Market Orientation and Entrepreneurship Orientation on Coffee Shop Performance, with Social Media as a moderating variable. This research was conducted at 49 Coffee Shops in Jambi City, using a questionnaire method to collect data. The analysis tool used is SmartPLS. The research results show that Market Orientation has no significant effect on Coffee Shop Performance, with a T-statistics value of 0.059 and a P-value of 0.477. On the other hand, Entrepreneurial Orientation has a positive and significant influence on Coffee Shop Performance, with a T-statistics value of 1.797 and a P-value of 0.036. Social Media has also been proven to have a positive and significant influence on Coffee Shop Performance, with a T-statistics value of 2,276 and a P-value of 0.011. In addition, this research found that Social Media does not moderate the influence of Market Orientation on Coffee Shop Performance, with a T-statistics value of 0.039 and a P-value of 0.484. However, Social Media moderates the influence of Entrepreneurial Orientation on Coffee Shop Performance, with a T-statistics value of 2.019 and a P-value of 0.022. These findings indicate that Entrepreneurial Orientation and the use of Social Media play an important role in improving Coffee Shop Performance. Therefore, Coffee Shop owners are expected to increase their entrepreneurial orientation and utilize social media more effectively to achieve better performance. Keywords: Market Orientation, Entrepreneurship Orientation, Social Media and Coffee Shop Performance.